2021
DOI: 10.1590/s0004-2803.202100000-26
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Screening Survey on the Seroprevalence of Hepatitis B and Hepatitis C Amongst the General Population of Rural Districts of Sindh, Pakistan

Abstract: BACKGROUND: Viral hepatitis is a global phenomenon, with the disease burden varying on a daily basis. Amongst chronic infections, hepatitis B virus and hepatitis C virus (HCV) are egregiously linked to severe health-related complications, with a worldwide prevalence of 248 million and 71 million respectively. Amongst the developing world, a hand full of countries are exhibiting a gross decline in chronic viral infection prevalence, like Bangladesh. While countries such as India have a consistent prevalence, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This high prevalence was also reported for HBV and HCV respectively in the present study but the target population was different and risk factors were not identified in this study. 7 An International Retrospective Quantitative Brazilian study found high seroprevalence of HBsAg among the prenatal mothers without any significant correlation of age and positivity ratio. However, there was a direct association between HBsAg and last four years of study testing.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This high prevalence was also reported for HBV and HCV respectively in the present study but the target population was different and risk factors were not identified in this study. 7 An International Retrospective Quantitative Brazilian study found high seroprevalence of HBsAg among the prenatal mothers without any significant correlation of age and positivity ratio. However, there was a direct association between HBsAg and last four years of study testing.…”
Section: Discussionmentioning
confidence: 97%
“…76%. 7 A Brazilian study showed high prevalence of Hepatitis-B among pregnant females. 8 An Ethiopian study showed 4.7% prevalence of Hepatitis B infection among the pregnant females and history of a surgical procedure, blood transfusion, multiple sexual partners and surgical procedure as risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Total population evaluated in these 8 studies comprises 150,897 with a mean Anti HCV prevalence of 12.98% having minimum prevalence of 4.9% and maximum prevalence of 20.1%. [6][7][8][9][10][11][12][13][14][15].…”
Section: Community Prevalencementioning
confidence: 99%